Application of Tuning Fork Sensors for In-situ Studies of Dynamic Force Interactions Inside Scanning and Transmission Electron Microscopes - Jana ANDZANE; Raimonds POPLAUSKS; Juris PRIKULIS; Rünno LÕHMUS; Sergey KUBATKIN; Donats ERTS (Medžiagotyra, 2012)
Mechanical properties of nanoscale contacts have been probed in-situ by specially developed force sensor based on a quartz tuning fork resonator (TF). Additional control is provided by observation of process in scanning electron microscope (SEM) and transmission electron microscope (TEM). A piezoelectric manipulator allows precise positioning of atomic force microscope (AFM) probe in contact with another electrode and recording of the TF oscillation amplitude and phase while simultaneously visualizing the contact area in electron microscope. Electrostatic control of interaction between the electrodes is demonstrated during observation of the experiment in SEM. In the TEM system the TF sensor operated in shear force mode: Use of TEM allowed for direct control of separation between electrodes. New opportunities for in situ studies of nanomechanical systems using these instruments are discussed. DOI: http://dx.doi.org/10.5755/j01.ms.18.2.1927